2008
DOI: 10.1007/s11251-008-9079-0
|View full text |Cite
|
Sign up to set email alerts
|

Observational learning from animated models: effects of studying–practicing alternation and illusion of control on transfer

Abstract: Animated models explicating how a problem is solved and why a particular method is chosen are expected to be effective learning tools for novices, especially when abstract cognitive processes or concepts are involved. Cognitive load theory was used to investigate how learners could be stimulated to engage in genuine learning activities. It was hypothesized that illusion of control would impede transfer performance compared to a condition without illusion of control. Moreover, we hypothesized that learners who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 44 publications
(50 reference statements)
1
14
0
1
Order By: Relevance
“…Most research demonstrating the borrowing and reorganizing principle is based on individual learning environments using worked examples (e.g., Cooper and Sweller 1987;Paas 1992;Paas and Van Gog 2006;Paas and Van Merriënboer 1994b;Renkl 1997;Sweller 1988;Sweller and Cooper 1985;Tuovinen and Sweller 1999) and animated models (e.g., Wouters et al 2008Wouters et al , 2009Wouters et al , 2010. However, the principle also applies to any information obtained from another human, resulting in collaborative learning environments providing us with an ideal example of the principle at work.…”
Section: The Collective Working Memory Effectmentioning
confidence: 99%
“…Most research demonstrating the borrowing and reorganizing principle is based on individual learning environments using worked examples (e.g., Cooper and Sweller 1987;Paas 1992;Paas and Van Gog 2006;Paas and Van Merriënboer 1994b;Renkl 1997;Sweller 1988;Sweller and Cooper 1985;Tuovinen and Sweller 1999) and animated models (e.g., Wouters et al 2008Wouters et al , 2009Wouters et al , 2010. However, the principle also applies to any information obtained from another human, resulting in collaborative learning environments providing us with an ideal example of the principle at work.…”
Section: The Collective Working Memory Effectmentioning
confidence: 99%
“…Some empirical studies have pointed to the moderating role of prior knowledge (Reisslein et al 2006;Wouters et al 2010). In the study by Reisslein et al, the factor of prior knowledge was even systematically varied to ascertain its influence, revealing that participants with low prior knowledge benefitted most from the classic instructional set-up in which instructions were followed by practice.…”
Section: Demonstration-based-training (Dbt)mentioning
confidence: 99%
“…score prior knowledge: 12, near transfer: 8, far transfer: 4). No partial credit was given and computational errors were ignored (for more details on the scoring procedure, see Wouters et al, 2009Wouters et al, , 2010. Efficiency on both the near and the far transfer test was calculated using the formula developed by Paas and Van Merriënboer (1993), but with test performance and mental effort invested in studying the animated examples (i.e., efficiency in terms of learning process, where a high efficiency denotes equal/low investment of effort during learning combined with high/equal performance on the test; see Van Gog & Paas, 2008).…”
Section: Scoringmentioning
confidence: 99%
“…However, research on the expertise reversal effect Expertise Reversal Effect of Animation Segmentation 4 (e.g., Wetzels, Kester, & Van Merriënboer, this issue; see for a review Kalyuga, Ayres, Chandler, & Sweller, 2003) has shown that measures that have a positive effect on efficiency and effectiveness for students with lower levels of prior knowledge might have no, or even a negative, effect on efficiency and effectiveness for students with higher levels of prior knowledge. This study investigates whether an expertise reversal effect of segmentation occurs with animated worked-out examples on probability calculation (see Wouters et al, 2009Wouters et al, , 2010.…”
mentioning
confidence: 99%